Pengaruh Penerapan Sistem Keuangan Desa (SISKEUDES) Terhadap Pengelolaan Keuangan Desa di Kecamatan Nita - Yuvensius Venerandus Nurak; Wilhelmina Mitan; Emilianus Eo Kutu Go’o (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of utilizing the village financial system on village financial management in Nita District. The method used in this study is a quantitative method with primary data sources in the form of questionnaires distributed to village officials using the Siskeudes application with a total of 32 respondents. The analytical method in this research is data quality test, classic assumption test, simple regression analysis, hypothesis testing and coefficient of determination. The results obtained in this study show that the village financial system (SISKEUDES) has no effect on village financial management in villages in Nita District. This shows that village financial management in villages in Nita District, Sikka Regency is largely not affected by the presence or absence of the Siskeudes application.